Bicentenary: Turning 200. Issue 2 (1st April 2020) - Rees, Martin
Abstract : Astronomer Royal Martin Rees spoke about the past and the future at the celebration of the bicentenary of the RAS Abstract: The Astronomer Royal, Martin Rees, spoke about the past and the future at the celebration of the bicentenary of the Royal Astronomical Society on 23 January 2020.